Clergy Sexual Abuse Litigation: The Policymaking Role of Tort Law - Lytton, Timothy D. (2007)
By all accounts, the prevalence of clergy sexual abuse and its cover-up by Church officials represents a massive institutional failure. Obscured by all of this attention to the Church's failure is the largely untold story of the tort system's remarkable success in bringing the scandal to light in the first place, focusing attention on the need for institutional reform, and spurring Church leaders and public officials into action. Tort litigation framed the problem of clergy sexual abuse as one of institutional failure, and it placed that problem on the policy agendas of the Catholic Church, law enforcement, and state governments. This Article examines these framing and agenda-setting effects of clergy sexual abuse litigation. It argues that private lawsuits can have a powerful and beneficial effect on policymaking